DUTIES OF NURSES IN THE FIELD OF ROBOTIC SURGERY. ADVANTAGES AND PERSPECTIVES - Diana Paskaleva; Vasilka Gyurova-Kancheva; Daniela Taneva (Journal of IMAB)
Background: The integration of robotic surgery into modern medical practices has transformed operative methodologies, necessitating an evolution in the roles of operating room nurses. Methods: The method of literature review through deductive content analysis was used for the study. Three databases were selected according to criteria scale and possibility of free access – Science Direct, PubMed (Medline), Scopus. Keywords/phrases corresponding to MeSH terminology (Medical Subject Headings) have been defined - ''robot surgery'', ''nurses'', ''robot assisted surgery'', ''nursing care'', ''laparoscopic surgery'', ''nurse's role'' Results: The literature review yielded 10 selected publications for analysis. These publications covered diverse topics such as nurses' experiences in robotic-assisted surgery, perioperative nursing roles, and evaluations of nursing interventions in robotic procedures. Conclusion: Nurses play main roles in robotic surgery across preoperative, intraoperative and postoperative phases. As technology advances, nurses need continuous training and updated protocols to meet the specific demands of robotic procedures. The study emphasizes the wide-ranging responsibilities of nurses and calls for ongoing research to enhance their contribution to the evolving field of robotic surgery.